Phosphorus-based negative electrode material with solid electrolyte interface and preparation method and application thereof
By forming a solid electrolyte interface of metal fluoride on the surface of the phosphorus carbon anode material, the problem of volume expansion and interface failure of the phosphorus carbon anode material during circulation is solved, and the cycle stability and rate performance of the battery are improved.
Patent Information
- Application Number
- CN202411799378.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-09
AI Technical Summary
The existing phosphorus carbon anode materials have volume expansion and interface damage during the circulation process, resulting in serious battery capacity decay and limited improvement in rate performance.
By mixing phosphorus powder, carbon material and metal fluoride particles and ball milling, a solid electrolyte interface with high strength and high lithium ion/electron transport is constructed to enhance the strength of the interface and reduce impedance.
The cycle stability and rate performance of phosphorus carbon anode material have been improved, extending the cycle life of the battery and improving capacity retention rate.
Smart Images

Figure CN119725434A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of battery materials, and in particular to a phosphorus-based negative electrode material with a solid electrolyte interface and a preparation method and application thereof. Background Art
[0002] As the market demands higher and higher energy density of batteries, developing negative electrode materials with high specific capacity is an effective means. Among them, phosphorus-carbon negative electrode has high specific capacity and excellent electronic conductivity, making it a current research hotspot and development direction. However, phosphorus particles have large volume expansion, and risks such as excessive thickness of pole pieces and electrode pulverization will lead to a decline in battery cell performance.
[0003] In the prior art, in order to solve the problem of volume expansion of phosphorus, the commonly used technical means is to compound with carbon materials such as graphite to form a phosphorus-carbon negative electrode, usually forming a phosphorus-carbon bond to inhibit the volume expansion of phosphorus during lithium storage. In addition, while compounding with carbon materials, metal elements can also be doped to improve conductivity, while helping to form a large number of PC bonds to improve lithium storage performance and maintain the structural stability of phosphorus. Or the volume expansion problem of phosphorus can be improved by constructing a carbon skeleton. However, these methods cannot solve the interface problem of phosphorus well, and the rate performance improvement is also limited. At present, new technical means are urgently needed to solve the volume expansion and rate performance of phosphorus-based materials. How to construct an electrolyte interface with excellent performance is the key to the excellent electrochemical properties of phosphorus-carbon materials. Summary of the invention
[0004] The present application provides a phosphorus-based negative electrode material with a solid electrolyte interface and a preparation method and application thereof. In the ball milling process, metal fluoride particles, carbon materials and phosphorus are added to in situ to construct a high-strength and high lithium ion / electron transmission solid electrolyte interface, thereby improving the cycle stability and rate performance of the battery. Lithium fluoride with high Young's modulus is used to enhance the strength of the solid electrolyte interface to inhibit the expansion of the phosphorus-carbon negative electrode, thereby improving the cycle stability.
[0005] In order to solve the above technical problems, in the first aspect, an embodiment of the present application provides a method for preparing a phosphorus-based negative electrode material with a solid electrolyte interface, comprising the following steps: first, phosphorus powder, carbon material and metal fluoride particles are mixed and ball-milled to obtain a composite negative electrode material; then, the composite material is sieved to obtain a phosphorus-based composite material.
[0006] In some exemplary embodiments, the metal fluoride includes a transition metal fluoride.
[0007] In some exemplary embodiments, the metal fluoride includes one or more of antimony fluoride, bismuth fluoride, tin fluoride, and indium fluoride.
[0008] In some exemplary embodiments, the phosphorus material includes one or more of black phosphorus, red phosphorus, and purple phosphorus.
[0009] In some exemplary embodiments, the carbon material includes one or more of graphite, carbon nanotubes, graphene, and graphyne.
[0010] In some exemplary embodiments, when phosphorus powder, carbon material and metal fluoride particles are mixed, the mass ratio of phosphorus powder, carbon material and metal fluoride is (80% to 50%): (50% to 5%): (20% to 2%).
[0011] In some exemplary embodiments, phosphorus powder, carbon material and metal fluoride are ball-milled in a ball mill; wherein the ball-to-material mass ratio of the ball milling is (80-10):1, the rotation speed is 200 r / min-800 r / min, and the ball milling time is 12 h-48 h.
[0012] In some exemplary embodiments, the particle size of the phosphorus-based negative electrode material is 200 mesh to 1000 mesh.
[0013] In the second aspect, the embodiments of the present application also provide a phosphorus-based negative electrode material with a solid electrolyte interface, which is prepared by the preparation method of the phosphorus-based negative electrode material with a solid electrolyte interface described in the above embodiments; the phosphorus-based negative electrode material includes a phosphorus / carbon-based negative electrode material core, and a metal fluoride-rich coating layer located on the surface of the core.
[0014] In addition, the embodiments of the present application also provide an application of the phosphorus-based negative electrode material with a solid electrolyte interface as described in the above embodiments in lithium-ion batteries, sodium-ion batteries, and potassium-ion batteries.
[0015] The technical solution provided by the embodiments of the present application has at least the following advantages:
[0016] The embodiment of the present application provides a phosphorus-based negative electrode material with a solid electrolyte interface and a preparation method and application thereof, the method comprising the following steps: first, phosphorus powder, carbon material and metal fluoride are mixed and ball-milled to obtain a composite negative electrode material; then, the composite negative electrode material is sieved to obtain a phosphorus-based negative electrode material. The present application uses a ball milling method to prepare a composite negative electrode material using phosphorus, carbon and metal fluoride as raw materials. Compared with the ball milling of single phosphorus and carbon, the preparation method of the present application forms metal fluoride on the surface of the phosphorus-carbon negative electrode. The composite material forms a layer of fluoride-rich metal with the surface during the cycle process, and is easy to form a fluoride-rich and metal alloy solid electrolyte interface layer during the cycle process. The in-situ interface layer has the following characteristics: high Young's modulus and low impedance. The interface layer is conducive to improving the cycle stability and rate capability of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] One or more embodiments are exemplarily described by pictures in the corresponding drawings, and these exemplifications do not constitute limitations on the embodiments. Unless otherwise stated, the pictures in the drawings do not constitute proportional limitations.
[0018] Figure 1 It is a flow chart of a method for preparing a phosphorus-based negative electrode material with a solid electrolyte interface provided in an embodiment of the present application.
[0019] Figure 2 It is a schematic diagram of the preparation process of the phosphorus-carbon negative electrode material provided in the embodiment of the present application.
[0020] Figure 3 This is a schematic diagram of a phosphorus-carbon negative electrode that constructs a solid electrolyte interface in situ during a cycle, as provided in an embodiment of the present application.
[0021] Figure 4 BP-G-CNT-SbF prepared in Example 1 of the present application 3 SEM image of .
[0022] Figure 5 BP-G-CNT-SbF in Example 1 of this application 3 TEM image of the composite material.
[0023] Figure 6 BP-G-CNT-SbF in Example 1 and Comparative Example 1 of the present application 3 XRD comparison diagram of BP-G-CNT composite material.
[0024] Figure 7 BP-G-CNT-SbF in Example 1 and Comparative Example 1 of the present application 3 EIS comparison chart with BP-G-CNT composite material.
[0025] Figure 8 BP-G-CNT-SbF in Example 1 and Comparative Example 1 of the present application 3 Cycle comparison with BP-G-CNT composite material.
[0026] Fig. 9 BP-G-CNT-SbF in Example 1 and Comparative Example 1 of the present application 3 Comparison of magnification with BP-G-CNT composite material.
[0027] Fig.10 BP-G-CNT-SbF in Example 1 and Comparative Example 1 of the present application 3 Interface comparison with BP-G-CNT composite material after 350 cycles. DETAILED DESCRIPTION
[0028] As can be seen from the background technology, the electrochemical performance of carbon materials can be improved by combining carbon materials with phosphorus or adding metal particles to form phosphorus-carbon materials. However, the phosphorus-carbon materials will still expand in volume and their interfaces will be destroyed during the cycle, resulting in serious capacity decay in the later stages of the cycle.
[0029] In order to solve the above technical problems, the embodiment of the present application provides a phosphorus-based negative electrode material with a solid electrolyte interface and a preparation method and application thereof, the method comprising the following steps: first, phosphorus powder, carbon material and metal fluoride are mixed and ball-milled to obtain a composite negative electrode material; then, the composite negative electrode material is sieved to obtain a phosphorus-based negative electrode material. The present application requires that while constructing a phosphorus-carbon negative electrode by grinding, metal fluoride is formed on the surface of the phosphorus-carbon negative electrode, and a solid electrolyte with high Young's modulus and low impedance characteristics is formed during the cycle to protect the inner layer of the phosphorus-carbon negative electrode, so that the patent has excellent cycle stability and rate performance.
[0030] The following will describe the various embodiments of the present application in detail with reference to the accompanying drawings. However, it will be appreciated by those skilled in the art that in the various embodiments of the present application, many technical details are provided in order to enable the reader to better understand the present application. However, even without these technical details and various changes and modifications based on the following embodiments, the technical solution claimed in the present application can be implemented.
[0031] See also Figure 1 The present invention provides a method for preparing a phosphorus-based negative electrode material having a solid electrolyte interface, comprising the following steps:
[0032] Step S1: Phosphorus powder, carbon material and metal fluoride particles are mixed and ball-milled to obtain a composite negative electrode material.
[0033] Step S2: Screening the composite material to obtain a phosphorus-based composite material.
[0034] In some embodiments, when phosphorus powder, carbon material and metal fluoride particles are mixed, the mass ratio of phosphorus powder, carbon material and metal fluoride is (80% to 50%): (50% to 5%): (20% to 2%).
[0035] The preparation method of the present invention is economical, simple, efficient and easy to operate. The present invention obtains a phosphorus / carbon / metal composite negative electrode material by adding metal fluoride and phosphorus and carbon materials under ball milling, and obtains the optimal hybridization range of phosphorus, carbon and metal fluoride (80% to 50%): (50% to 10%): (20% to 2%). At a current density of 1A / g, it can still provide 1006.88mAh g after 350 cycles. -1 The capacity retention rate is 66.23%. -1The composite material can still provide 893.84 mAh g -1 The preparation process is easy to control and the battery performance is excellent, which is conducive to industrial production and application.
[0036] This application constructs a high-strength and high lithium ion / electron transport solid electrolyte interface in situ by incorporating metal fluorides, thereby improving the battery's cycle stability and rate performance. When a lithium-ion battery is discharged, the metal fluoride can construct a solid electrolyte interface rich in lithium fluoride with high Young's modulus and lithium-metal alloy with high ion / electronic conductivity in situ on the surface of phosphorus-carbon particles before lithium is embedded in phosphorus-carbon. It can enhance the strength of the solid electrolyte interface with the help of lithium fluoride with high Young's modulus to inhibit the expansion of the phosphorus-carbon negative electrode, thereby improving the cycle stability. At the same time, the impedance of the solid electrolyte interface is reduced with the help of lithium-metal alloys with high ion / electronic conductivity, thereby improving the rate performance.
[0037] In some embodiments, the metal fluoride comprises a transition metal fluoride.
[0038] In some embodiments, the metal fluoride includes one or more of antimony fluoride, bismuth fluoride, tin fluoride, and indium fluoride.
[0039] In some embodiments, the phosphorus material includes one or more of black phosphorus, red phosphorus, and purple phosphorus.
[0040] In some embodiments, the carbon material includes one or more of graphite, carbon nanotubes, graphene, and graphyne.
[0041] In some embodiments, phosphorus powder, carbon material and metal fluoride are ball-milled in a ball mill; wherein the ball-to-material mass ratio of the ball milling is (80-10):1, the rotation speed is 200r / min-800r / min, and the ball milling time is 12h-48h.
[0042] In some embodiments, the particle size of the phosphorus-based negative electrode material is 200 mesh to 1000 mesh.
[0043] The present application provides a method for preparing a phosphorus-based negative electrode material having a solid electrolyte interface, and the specific steps are as follows:
[0044] (1) Weigh black phosphorus, carbon material, and metal fluoride according to a certain mass ratio in an argon atmosphere glove box and place them into a 100 mL zirconium oxide jar.
[0045] (2) The zirconia tank is filled with 15mm:8mm:5mm zirconia balls in a mass ratio of 1:2:4.
[0046] (3) Use a planetary ball mill to mill at a certain speed for a period of time to obtain a uniform material product.
[0047] (4) The ball milled product is introduced into a 200-mesh sieve for sieving to screen out the final fluoride-doped metal fluoride / phosphorus / carbon composite material.
[0048] Example 1
[0049] (1) Black phosphorus, graphite, carbon nanotubes, and antimony fluoride were weighed into a 100 mL zirconium oxide can in an argon atmosphere glove box at a mass ratio of 65:20:10:5.
[0050] (2) The zirconia tank contained 15 mm:8 mm:5 mm zirconia balls in a mass ratio of 1:2:4, which were 42.85 g, 85.71 g, and 171.43 g, respectively.
[0051] (3) Use a planetary ball mill at 350 rpm for 24 h.
[0052] (4) The ball milled product is introduced into a 200-mesh screen for sieving to screen out the final antimony fluoride-doped black phosphorus / graphite / carbon nanotube composite material. The morphology and transmission electron microscopy image (including element distribution map) of the prepared material are as follows: Figure 4 and Figure 5 shown.
[0053] Comparative Example 1
[0054] The difference between this comparative example 1 and the example 1 is that antimony fluoride is not added. That is, the ratio of black phosphorus, graphite and carbon nanotubes is 70:20:10. The crystal structure of the comparative example 1 is shown in FIG. Figure 6 shown.
[0055] Comparative Example 2
[0056] The difference between Comparative Example 2 and Example 1 is that the phosphorus raw material is red phosphorus material.
[0057] Comparative Example 3
[0058] The difference between Comparative Example 3 and Example 1 is that the carbon material selected is a single graphite material.
[0059] Comparative Example 4
[0060] The difference between Comparative Example 4 and Example 1 is that the metal fluoride is bismuth fluoride.
[0061] Comparative Example 5
[0062] The difference between Comparative Example 5 and Example 1 is that the metal fluoride is tin fluoride.
[0063] Comparative Example 6
[0064] The difference between Comparative Example 6 and Example 1 is that the content of black phosphorus is 80%, that is, the proportion of black phosphorus, graphite and carbon nanotubes is added in a mass ratio of 80:20:10:5.
[0065] Comparative Example 7
[0066] The difference between Comparative Example 7 and Example 1 is that the content of black phosphorus is 50%, that is, the ratio of black phosphorus, graphite and carbon nanotubes is 50:20:10:5 by mass.
[0067] Comparative Example 8
[0068] The difference between Comparative Example 8 and Example 1 is that the carbon content is changed, that is, the ratio of black phosphorus, graphite and carbon nanotubes is added in a mass ratio of 65:14:6:5.
[0069] Comparative Example 9
[0070] The difference between this comparative example 9 and example 1 is that the content of the fluoride metal material is changed, that is, the ratio of black phosphorus, graphite and carbon nanotubes is added in a mass ratio of 65:20:10:2.
[0071] Comparative Example 10
[0072] The difference between Comparative Example 10 and Example 1 is that the content of the fluoride metal material is changed, that is, the ratio of black phosphorus, graphite and carbon nanotubes is added in a mass ratio of 65:20:10:20.
[0073] Example 1 and Comparative Examples 1-10 were assembled into lithium-ion batteries, numbered as Battery 0, Battery A~J respectively. Among them, the battery structure: the battery structure of this experiment is a half-cell also called a button cell. The working electrode includes an electrode current collector and an active material layer (metal fluoride / phosphorus / carbon material) on its surface, the counter electrode is a metal lithium sheet, the middle is a diaphragm, and the inside of the steel shell is filled with electrolyte. The electrode current collector is a copper foil with a thickness of 10μm, the diaphragm is a PE-based film with a thickness of 5μm, and the surface is coated with a PVDF oil-based diaphragm with a thickness of 1μm; the components of the electrolyte: a mixture of EC, DEC, LiPF6, FEC and LiOFB with a mass ratio of 40:40:12:5:3; the preparation method of the working electrode comprises: preparing an electrode material slurry containing a phosphorus-based material, a binder (PVDF) and a conductive agent (acetylene black), and applying the slurry to the surface of the electrode current collector to obtain a working electrode, wherein the mass density of the electrode material coating is 1.5mg / cm 2 , the electrode coating thickness is 100 μm; the mass ratio of phosphorus-based material, binder (PVDF) and conductive agent (acetylene black) is 8:1:1.
[0074] To test the electrochemical performance, the cycle test method includes: constant current charge and discharge on a blue electric test system: cycle 350 times at a current density of 1A / g in the voltage range of 0-2.5V. Table 1 shows the cycle performance and interface data of the phosphorus-based negative electrode materials in Example 1 and Comparative Examples 1 to 10 of the present application. The test result graph is shown in Table 1 below, where the interface impedance, cycle performance, rate performance and interface performance after cycling of the black phosphorus / carbon nanotube / graphite metal fluoride in Example 1 and the black phosphorus / carbon nanotube / graphite in Comparative Example 1 are shown respectively. Figure 7 , Figure 8 , Fig. 9 and Fig.10 These indicate that BP-G-CNT-SbF 3 With lower interface impedance (such as Figure 7 Example 1 (BP-G-CNT-SbF 3 ) After 350 cycles, the discharge capacity is still 1006 mAh g -1 , the capacity retention rate is 66.2%, while the capacity retention rate of the comparative example BP-G-CNT is 13.7% (e.g. Figure 8 Example 1 has better rate performance (as shown). Fig. 9 as shown), and a more complete loop interface after looping.
[0075] Table 1 Electrochemical performance results of phosphorus-based anodes obtained by different preparation processes
[0076]
[0077]
[0078] From Example 1 and Comparative Example 1, it can be seen that without adding metal fluoride, the LiF interface layer with high mechanical strength cannot be formed during the cycle of battery A, and the integrity of the electrode material cannot be effectively guaranteed. At the same time, the capacity is low.
[0079] By comparing Example 1 with Comparative Example 2, the performance of Battery B is worse than that of Battery 0, which is determined by the cycle performance of red phosphorus and black phosphorus. Black phosphorus has excellent electrochemical properties and conductivity, while red phosphorus has low conductivity.
[0080] It can be seen from Example 1 and Comparative Example 2 that when the single carbon material is only graphite, its capacity retention rate is found to be low. This is because carbon nanotubes have excellent electrical conductivity and certain flexibility, which can ensure the stability of the electrode structure and thus improve its cycle stability.
[0081] It can be seen from Example 1 and Comparative Examples 4-5 that the capacity utilization and capacity retention of batteries D and E are both low. This is because during the cycle, bismuth fluoride can be embedded in lithium before phosphorus and carbon to form a lithium-bismuth alloy to increase lithium ion conductivity, but the lithium removal is earlier than phosphorus and carbon, and cannot play a significant role. The tin reaction potential is around 0.2-0.3V, which is later than phosphorus and carbon embedding lithium. The alloy formed cannot improve the conductivity when phosphorus and carbon embedding lithium.
[0082] By comparing Example 1 with Comparative Examples 6 and 7, it can be seen that the initial capacity of batteries F and G is related to the black phosphorus content. The higher the black phosphorus content, the higher the first-cycle capacity. However, too much black phosphorus will lead to a decrease in its cycle stability, and too little black phosphorus will lead to a low capacity.
[0083] Compared with Example 1, Comparative Example 8 reduces the carbon content, resulting in an increase in its initial capacity but a decrease in the carbon layer coating effect, resulting in a decrease in cycle stability.
[0084] It can be seen from Example 1 and Comparative Examples 9 and 10 that when the metal fluoride is reduced, an effective solid electrolyte layer cannot be formed, resulting in poor cycle stability. When the metal fluoride is increased, the capacity is reduced and the cycle stability is slightly increased.
[0085] The present application also provides a phosphorus-based negative electrode material with a solid electrolyte interface, which is prepared by the method for preparing the phosphorus-based negative electrode material with a solid electrolyte interface described in the above embodiment; Figure 2 As shown, the phosphorus-based negative electrode material includes a phosphorus / carbon-based negative electrode material core and a metal fluoride-rich coating layer located on the surface of the core.
[0086] In addition, the embodiments of the present application also provide an application of the phosphorus-based negative electrode material with a solid electrolyte interface as described in the above embodiments in secondary batteries such as lithium-ion batteries, sodium-ion batteries, and potassium-ion batteries.
[0087] The embodiment of the present application provides a phosphorus-based negative electrode material with a solid electrolyte interface and a preparation method and application thereof, the method comprising the following steps: first, phosphorus powder, carbon material and metal fluoride are mixed and ball-milled to obtain a composite negative electrode material; then, the composite negative electrode material is sieved to obtain a phosphorus-based negative electrode material. The present application uses a ball milling method to prepare a composite negative electrode material using phosphorus, carbon and metal fluoride as raw materials. Compared with the ball milling of single phosphorus and carbon, the preparation method of the present application forms metal fluoride on the surface of the phosphorus-carbon negative electrode. The composite material forms a layer of fluoride-rich metal with the surface during the cycle process, and is easy to form a fluoride-rich and metal alloy solid electrolyte interface layer during the cycle process. The in-situ interface layer has the following characteristics: high Young's modulus and low impedance. The interface layer is conducive to improving the cycle stability and rate capability of the material.
[0088] Those skilled in the art will appreciate that the above-mentioned embodiments are specific examples for implementing the present application, and in practical applications, various changes may be made to the embodiments in form and detail without departing from the spirit and scope of the present application. Any person skilled in the art may make their own changes and modifications without departing from the spirit and scope of the present application, and therefore the scope of protection of the present application shall be subject to the scope defined in the claims.
Claims
1. A method for preparing a phosphorus-based negative electrode material having a solid electrolyte interface, characterized in that: The following steps are involved: The phosphorus powder, the carbon material and the metal fluoride particles are mixed and ball-milled to obtain a composite negative electrode material; The composite material is sieved to obtain a phosphorus-based composite material.
2. The method for preparing a phosphorus-based negative electrode material having a solid electrolyte interface according to claim 1, characterized in that: The metal fluoride includes a transition metal fluoride.
3. The method for preparing a phosphorus-based negative electrode material having a solid electrolyte interface according to claim 1, characterized in that: The metal fluoride includes one or more of antimony fluoride, bismuth fluoride, tin fluoride and indium fluoride.
4. The method for preparing a phosphorus-based negative electrode material having a solid electrolyte interface according to claim 1, characterized in that: The phosphorus material includes one or more of black phosphorus, red phosphorus and purple phosphorus.
5. The method for preparing a phosphorus-based negative electrode material having a solid electrolyte interface according to claim 1, characterized in that: The carbon material includes one or more of graphite, carbon nanotubes, graphene, and graphyne.
6. The method for preparing a phosphorus-based negative electrode material having a solid electrolyte interface according to claim 1, characterized in that: When the phosphorus powder, the carbon material and the metal fluoride particles are mixed, the mass ratio of the phosphorus powder, the carbon material and the metal fluoride is (80% to 50%): (50% to 5%): (20% to 2%).
7. The method for preparing a phosphorus-based negative electrode material having a solid electrolyte interface according to claim 1, characterized in that: Phosphorus powder, carbon material and metal fluoride are ball-milled in a ball mill; wherein the ball-to-material mass ratio is (80-10):1, the rotation speed is 200 r / min-800 r / min, and the ball milling time is 12 h-48 h.
8. The method for preparing a phosphorus-based negative electrode material having a solid electrolyte interface according to claim 1, characterized in that: The particle size of the phosphorus-based negative electrode material is 200 mesh to 1000 mesh.
9. A phosphorus-based negative electrode material with a solid electrolyte interface, characterized in that: The method for preparing a phosphorus-based negative electrode material with a solid electrolyte interface as described in any one of claims 1 to 8 is adopted; the phosphorus-based negative electrode material comprises a phosphorus / carbon-based negative electrode material core and a metal fluoride-rich coating layer located on the surface of the core.
10. Use of the phosphorus-based negative electrode material with a solid electrolyte interface as claimed in claim 9 in lithium ion batteries, sodium ion batteries and potassium ion batteries.
Citation Information
Patent Citations
Novel phosphorus-carbon negative electrode material based on red phosphorus and preparation method
CN115621445A
Composite electrode and preparation method and application thereof
CN118156422A
Phosphorus-based negative electrode material, preparation method thereof and lithium ion battery
CN118507671A
Fluorine-doped phosphorus-carbon composite negative electrode material and preparation method thereof
CN119050302A
Cited By
Composite electrode material and preparation method thereof
CN121609306A